Halal In The Contemporary Economic And Business Ecosystem - Nila Sulistiawati; Muhammad Said; Muniaty Aisyah (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The increase in population will certainly increase the demand for halal products and services significantly. With this achievement where Indonesia is in the top five with a strong Islamic economic ecosystem and supported by a majority Muslim population, Indonesia can become a leading country in all sectors in the country's halal industry (Nasution, 2020).The Islamic economic ecosystem in Indonesia continues to grow which includes the existence of UMKM that can become producers of halal products, Islamic finance which is marked by the growing contribution of Islamic entities, both Islamic financial institutions and Islamic non-financial institutions, innovations in technology, and related regulations with the halal industry. Indonesia is the first place for consumers of halal food products in the world. Indonesia is the country with the largest Muslim population, reaching 209.1 million people or 87.2 percent of the total population of Indonesia (Mubarok & Imam, 2020). Objective: prevention of aspects of sharia obstacles in the financial aspect, MSME aspects, digitalization aspects, product quality, and regulatory aspects in realizing the strengthening of the halal industrial ecosystem? Indonesia, the world's most populous Muslim country, is a gold mine for the halal market with the potential to become not only a major market but also a major producer of halal products. Islamic finance in Indonesia has developed more than the banking sector, but also non-banking products have featured in baitul mal wa tamwil (community-based Islamic financial institutions), Islamic insurance, Islamic microfinancing, Islamic pawnshops and Islamic venture capital. The Islamic banking service has almost all complied with sharia principles as most Islamic banking products are dominated by murabahah (sales contracts). There is still a small number of Islamic banks in Indonesia which causes Islamic banks to not reach remote areas (Samsul, 2022). There is still a lack of Sharia banking education for the